CPR knowledge and resuscitation self-efficacy among nurses across diverse healthcare settings in Saudi Arabia: a mixed-methods cross-sectional study - Jassem Almualem; Doaa Alabdulbaqi; Fatimah Alzain; Manal Bazboz; Amal Zahran; Zainab Alsaffar; Jawad Almzain; Lamees Almansour; Amal Alzaher; Heba Altalaq; Amnah Bawady; Zaher Alhabib; et al. (BMC Nursing, 2026)
Abstract Background Nurses are usually the first to reach a patient in cardiac arrest. Yet their CPR knowledge and perceived resuscitation self-efficacy — referred to together in this paper as resuscitation preparedness, since clinical performance was not measured — vary sharply from one clinical environment to another, and very little of this variation has been documented in Saudi Arabia. Aim To examine the relationship between CPR knowledge and self-efficacy among nurses across four distinct healthcare settings and to explore contextual barriers and facilitators influencing resuscitation preparedness. Methods A mixed-methods cross-sectional design was employed across healthcare facilities in the Eastern Province of Saudi Arabia, encompassing critical care units, inpatient wards, outpatient clinics, and primary healthcare centres (PHCs). Quantitative data were collected using the researcher-developed CPR/resuscitation knowledge test (20 items) and a 10-item resuscitation self-efficacy questionnaire adapted from Roh et al. (2012; α = 0.94 in the present sample; n = 227). Analyses included Pearson correlation, one-way ANOVA with Tukey post-hoc tests, multiple linear regression, and intraclass correlation coefficient (ICC) estimation. Qualitative data were gathered through 22 semi-structured interviews analysed using Braun and Clarke’s [1] thematic framework. Results A significant positive correlation was identified between CPR knowledge and self-efficacy ( r = .321, p < .001), with knowledge explaining 10.3% of self-efficacy variance (unstandardised b = 0.592, p < .001). Significant inter-setting differences were found in both knowledge (F = 4.42, p = .005, η² = 0.056) and self-efficacy (F = 8.61, p < .001, η² = 0.104), with critical care nurses scoring highest (SE: M = 44.30, SD = 6.75) and outpatient clinic nurses lowest (SE: M = 37.74, SD = 5.43). The ICC point estimate was 0.122 (95% CI [0.030, 0.684]); with only four setting categories available for estimation, this estimate is exploratory. Six qualitative themes were identified: clinical exposure as the primary self-efficacy driver; fear of error and team dynamics as barriers; training for certification rather than competency; institutional support and debriefing as differentiating factors; psychological and emotional determinants; and contextual setting-level variation. Conclusions Differences in CPR knowledge and perceived self-efficacy across settings are not explained by knowledge deficits alone; psychological and organisational factors also appear to contribute. Outpatient and primary care environments in particular need training built around simulation, and a routine practice of debriefing after resuscitation events.